2020
DOI: 10.1016/j.ijid.2020.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of automated SARS-CoV-2 antigen test for COVID-19 infection with quantitative RT-PCR using 313 nasopharyngeal swabs, including from seven serially followed patients

Abstract: Highlights We assess the performance of the LUMIPULSE antigen test compared to RT-qPCR The antigen level was significantly higher in PCR-positive samples than in negative samples The antigen test determined all samples (>100 viral copies) to be positive Likewise, it determined 85% of samples (>10 viral copies) to be positive The kinetics of viral loads and antigen levels showed a similar declining trend

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
242
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(275 citation statements)
references
References 22 publications
24
242
8
1
Order By: Relevance
“…Interestingly, we observed an excellent correlation between the antigen signal and Ct values obtained by RT-PCR ( Figure 2 ). Hirotsu et al evaluated another automated AG test, namely the LUMIPULSE SARS-CoV-2 Ag kit (Fujirebio, Tokyo, Japan), performed on a LUMIPULSE G600II chemiluminescent assay [ 29 ]. Out of 58 RT-PCR positive patients, 26 (44.8%) were negative on the LUMIPULSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we observed an excellent correlation between the antigen signal and Ct values obtained by RT-PCR ( Figure 2 ). Hirotsu et al evaluated another automated AG test, namely the LUMIPULSE SARS-CoV-2 Ag kit (Fujirebio, Tokyo, Japan), performed on a LUMIPULSE G600II chemiluminescent assay [ 29 ]. Out of 58 RT-PCR positive patients, 26 (44.8%) were negative on the LUMIPULSE.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 58 RT-PCR positive patients, 26 (44.8%) were negative on the LUMIPULSE. The specificity of the test ranged from 97.3% to 99.6% [ 29 , 30 ]. They also observed a weaker correlation with viral load (i.e., R 2 = 0.77) compared to our evaluation with the VITROS automated assay (i.e., R 2 = 0.94), which in our hands, showed excellent clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of the first antigenic tests was significantly lower than that detected by the nucleic acids (56.2% (IC95%: 29.5-79.8%)) with a comparable specificity (99.5% (IC95% (98.1%-99.9%)) [25]). However, the new generation of antigenic tests present, during the first week of infection, comparable values of sensitivity and specificity [26][27][28]. It has been shown that for viral loads below 2 log copies/mL the correlation between antigen and molecular techniques is 100%, while it drops to 60% with viral loads of 1-2 log copies/mL, and to 33% with viral loads <1 log copies/mL.…”
Section: Procedures For Collecting Transporting and Storing The Nasopmentioning
confidence: 99%
“…It has been shown that for viral loads below 2 log copies/mL the correlation between antigen and molecular techniques is 100%, while it drops to 60% with viral loads of 1-2 log copies/mL, and to 33% with viral loads <1 log copies/mL. As a consequence, other factors related to viral load can be used as surrogate markers of the validity of antigen tests: i) duration of infection: during the first week of symptoms the sensitivity of the ADT is on average 93.9% (95% CI: 86.5-97.4%) [28]; ii) Ct index: the sensitivity of ADT is 98% (95% CI: 90-100%) for Ct ≤25, and 57% (95% CI: 48-65%) for Ct ≥30 [26,27] . According to these data it can be affirmed that ADT have special clinical utility in suspected cases during the first 5-7 days of symptoms.…”
Section: Procedures For Collecting Transporting and Storing The Nasopmentioning
confidence: 99%
“…Low-cost, rapid antigenbased tests [106,[114][115][116][117][118]121] POC platforms utilizing isothermal and RT-PCR tests [14,207] CRISPR-based lateral flow assay strips [43] Interpandemic Pandemic phase Interpandemic…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%